TOPOI Mobility: Accessibility and settlement types in the urban rural gradient of Lower Saxony - opportunities for sustainable mobility - Carlow, Vanessa Miriam; Mumm, Olaf; Neumann, Dirk; Schmidt, Nina; Siefer, Thomas (Urban, planning and transport research, 2021)
The accessibility of suburban and rural areas presents existential challenges for resident communities. Municipality inhabitants with little access to public transport and structurally weak regions often work in distant urban agglomerations, with long commutes. Widespread monofunctional 'dormitory' villages and suburban areas with low building density and access to public transport, fuelling automobility dependence, are still implemented as planning concepts in Lower Saxony. The objectives of this study are to analyse the quality of public transport accessibility along the urban-rural gradient in relation to settlement types in two regions in Lower Saxony; to identify the interrelations between good accessibility by public transport and population density; to identify opportunities and challenges of urban-rural public transport accessibility. The application of the settlement classification system TOPOI - developed to analyse and define settlement patterns in urban-rural gradients - enabled us to determine the quality of public transport. Furthermore, we newly developed the 'Public Transport Access Score' based on parameters such as available public transport modalities, their catchment areas, operating frequencies, and connectivity and applied it to demonstrate the level of accessibility for different settlement types of similar characteristics (TOPOI). Hence, we localised how sustainable accessibility of public transport can benefit the development of the urban-rural network.